The relationship between segmental trunk control and gross motor performance in low birth weight born infants - YURDALAN, SAADET UFUK (My University, 2022)
© 2022 Taylor & Francis Group, LLC.Objective: Trunk control is associated with gross motor development. This study examines the relationship between segmental trunk control and gross motor performance in low birth weight (LBW) infants Methods: A total of 42 LBW infants and 43 normal birth weight (NBW) infants aged 3–9 months were sampled for this cross-sectional study. All infants were evaluated one time by the Segmental Assessment Trunk Control (SATCo) and the Alberta Infant Motor Scale (AIMS) Results: Statistically high and significant correlations were found between gross motor performance and segmental trunk control in all sample populations (r = 0.835; p = .001). No statistically significant difference was found regarding the segmental trunk control between the groups (p = .119). The LBW infants with atypical motor development had poorer trunk control than the LBW infants with typical development (f = 5.480; p = .001). Conclusion: Our results show that LBW infants with atypical motor development had poorer trunk control than LBW infants with typical motor development. It was found that the segmental trunk controls of LBW infants were 0.398 times lower than in NBW infants.
Keywords: Tıp; Dahili Tıp Bilimleri; Fiziksel Tıp ve Rehabilitasyon; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Physical Medicine and Rehabilitation; Health Sciences; Klinik Tıp (MED); Klinik Tıp; REHABİLİTASYON; Clinical Medicine (MED); CLINICAL MEDICINE; REHABILITATION; Fizik Tedavi, Spor Terapisi ve Rehabilitasyon; Physical Therapy, Sports Therapy and Rehabilitation; Low birth weight; motor performance; posture; trunk control; POSTURAL ADJUSTMENTS; CHILDREN; Low birth weight; motor performance; posture; trunk control